Numerical simulation of circulating tumor cell separation in a dielectrophoresis based Y-Y shaped microfluidic device - Zhang, Xiangzhi; Xu, Xiawei; Ren, Yong; Yan, Yuying; Wu, Aiguo (2020)
Efficient and effective separation of circulating tumor cells from biological samples to promote early diagnosis of cancer is important but challenging, especially for non-small cell lung cancer (NSCLC). In this article, a Y-Y shaped microfluidic device was designed to isolate NSCLC cells with a dielectrophoresis approach. Numerical simulations were conducted that the trajectories of cells were traced by solving the electric potential distribution and the flow field in a microchannel. The effects of inlet flow rate ratio of blood sample and buffer on separation performance were studied and optimized by the numerical investigation. Under optimal operating conditions, the separation efficiency can reach around 99%, which is achieved with 100 kHz AC, electrodes potential ranging from 1.6 V to 2.2 V, and flow rate ratio from 1.9 to 2.5. This study presents a potentially efficient, facile and low-cost route for circulating tumor cell separation.